Strategi Lembaga Konsultasi Kesejahteraan Keluarga (LK3) Dinas Sosial Kota Palu dalam Memotivasi Penyandang Masalah Kesejahteraan Sosial - Yayan; S. Tahir, Lukman; Jusmiati (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2021)
This study aims to describe in full and in depth the social reality and various phenomena that occur in the society which is the subject of research so that the characteristics, characters, traits, and models of these phenomena are described. The main issues in this study are 1. How is the welfare of scavengers and beggars in Palu City 2. What factors affect the welfare, psychological and financial of scavengers and beggars. 3 What is the strategy of the Palu City Social Service Family Welfare Consultation Institute in motivating the welfare of scavengers and beggars. This research is classified as qualitative with the research approach used is a normative and sociological approach, namely environmental interactions that are in accordance with social units, individuals, groups, institutions, or communities. The data source of this research is the people of scavengers and beggars. Furthermore, the data collection methods used were observation, interviews, and documentation. Then the data processing and analysis techniques were carried out through three stages, namely: data reduction, data presentation and drawing conclusions. This study was carried out by checking the validity of the data with trigulation techniques. In an effort to improve people's welfare, these efforts cannot be separated from the Regional Medium-Term Development Plan (RPJMD). Based on this basis, the Palu City Social Service has adopted various policies to improve the welfare of the community, especially scavengers and beggars. In the study, it was found that the welfare of scavengers and beggars in Palu City by the Family Welfare Consultation Institute (LK3) is an increase in human and economic resources, by providing assistance in the form of rehabilitation and knowledge development to provide abilities to beggars and scavengers in Palu City. There are many factors behind the emergence of scavengers and beggars in people's lives. Based on the author's observations, the factors in the emergence of beggars and scavengers can be caused by 1. Poverty problems (Financial). 2 Educational problems. 3 Work skills problems. 4 Psychic Problems